The Review on current treatments and therapies on COVID-19: Formulation Development of Sustained Release Matrix Tablet - Bharad, Vaibhav R; Deshmukh, Omprasad R; Wagh, Swaraj M; Folane, Pavan; Kale, R H; Biyani, K R (Asian Journal of Pharmaceutical Research and Development, 2020)
Coronavirus are enveloped RNA Virus related to family ‘Coronaviride’. In December 2019, many pneumonia cases reported by patients with unknown causes mainly associated with seafood and wet market in when China and they are clinically resembled with viral pneumonia at present time there is no antiviral drug for the treatment of COV infection but some drugs and therapies gives effective action in the treatment and prevention of the SAR-COV-1 and MERS COV and these particular drugs and therapies plays important role in prevention and cure of SARS-COV-2 (COVID-19) such as Hydroxy-chloroquine and Chloroquine, Remdesivir, Ivermectin, Lopinavir/Ritonavir, Favipiravir and therapies may include convalescent plasma therapy and corticosteroids.Hydroxyl-chloroquine and chloroquine exibites its action against SARS-COV-2 by blocking the entry of viral cell inhibiting glycosylation of host receptor Ivermectin show anti SARS-COV-2 action by binding of Ivermectin to the imp α/β1 binding to viral proteins. This particular action prevents the viral from entering the nucleus which leads to reducing inhibition and antiviral response. Remdisivir (G-S5734) is an RdRP polymerase inhibitor and exhibites anti SARS-COV-2 action by inhibiting viral nucleic acid synthesis. Patients treated with convalscent plasma therapy and corticosteroids gives less mortality rate and has no adverse effect .The speed and volume of clinical preliminaries propelled research expected treatments for COVID-19 feature both the need and capacity to treat excellent proof even in pandemic no treatment demonstrate effective to date.